Effectiveness of suicide prevention gatekeeper training in nurses at a tertiary health care center in Nepal - Reecha Khadka; Mita Rana; Suraj Shakya; Avilasha Singh; Sanjay Yadav (BMC Psychiatry)
Abstract Background Suicide constitutes a significant public health concern in Nepal, characterized by a lack of comprehensive national preventive strategies and insufficient training for healthcare workers in assessing mental illness and suicidal behaviors. Nurses, as frontline healthcare providers, play a critical role in identifying patients at risk. This study aims to assess the effectiveness of a suicide gatekeeper training program for nurses, with a focus on improving self-efficacy and attitudes toward suicide prevention. Methods A single-group pretest-posttest study recruited 72 nurses from various clinical units of a tertiary care center. The intervention model consisted of a 2-hour suicide prevention gatekeeper training program developed at the same center. The program’s effectiveness was measured using gatekeeper self-efficacy and attitudes toward suicide scale prior to and one week after the training. A paired sample t-test was performed to compare the pretest and post-test results. Results Significant improvements were observed in both self-efficacy (d = 1.12) and attitudes (d = 0.05) after the training. While self-efficacy showed a large effect size, indicating substantial gains in confidence, attitude change was minimal. Significant differences were found across age groups and years of experience, with all groups showing improvements in self-efficacy and attitudes (p < 0.05 to p < 0.001). The median scores for all items of the self-efficacy tool showed a substantial rise from pretest to posttest. Conclusion The suicide prevention gatekeeper training program significantly improved nurses’ self-efficacy and attitudes toward suicide prevention, enhancing their ability to identify and manage suicide risks. However, the smaller effect on attitude change suggests that additional interventions may be needed for more substantial attitudinal shifts.